2003
DOI: 10.1016/s0002-9343(02)01568-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based order entry decreases duration of indwelling urinary catheterization in hospitalized patients

Abstract: U p to 25% of hospitalized patients will have an indwelling urinary catheter inserted (1). While most of these catheters are required for optimal patient care, about one in five is unnecessary (2). Catheter-related urinary tract infections are the leading cause of nosocomial infection. They account for up to 40% of hospital-acquired infections, with an incidence of 3% to 10% per day of indwelling catheterization (1,(3)(4)(5). Bacteremia occurs in 1% to 4% of those who develop nosocomial bacteriuria (6). Most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 21 publications
2
83
0
Order By: Relevance
“…1,5,6,8,15 Strategies to decrease the duration of catheterization have been recommended, such as reminding physicians to review whether a catheter is still appropriate and using automatic stop orders to facilitate the removal of catheters when the devices are no longer needed. 8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate.…”
Section: Characteristics Of the Patientsmentioning
confidence: 97%
See 1 more Smart Citation
“…1,5,6,8,15 Strategies to decrease the duration of catheterization have been recommended, such as reminding physicians to review whether a catheter is still appropriate and using automatic stop orders to facilitate the removal of catheters when the devices are no longer needed. 8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate.…”
Section: Characteristics Of the Patientsmentioning
confidence: 97%
“…8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate. In another study, using a randomized design, Loeb et al 20 found that use of automatic stop orders was not associated with a decrease in the incidence of UTIs.…”
Section: Characteristics Of the Patientsmentioning
confidence: 97%
“…62 Studies of the appropriateness of use of urinary catheters indicate that 21% to 38% of initial urinary catheterizations are unjustified, and one-third to one-half of days of continued catheterization are unjustified. [63][64][65] When inpatient physicians and students at 4 academic medical centers were asked whether or not each of their patients had a urinary catheter, they incorrectly reported that their patient did not have a catheter 28% of the time.…”
Section: Possibly Effective Strategiesmentioning
confidence: 99%
“…64 In a recent controlled study, instituting a computerized urinary catheter order and a computer-generated stop order 72 hours after insertion reduced the duration of catheterization by about one-third (3 days). 62 Thus, a computerized reminder system might reduce CAUTI by prompting removal of "forgotten" catheters. 32 If the urinary catheter cannot be removed, a possible solution is to move it from the urethra to another location.…”
Section: Possibly Effective Strategiesmentioning
confidence: 99%
“…In a systematic review of 80 patient-safety interventions, 16 those with reasonable supporting evidence consisted largely of clinical therapies such as prophylaxis of venous thromboembolism. Frequently espoused "systembased" interventions, such as improving facility design and work flow with technology and robotics, adding forcing functions to procedures (e.g., automatic stop orders for Foley catheters 17 or precautions against the storage of concentrated potassium solutions with ward stock) 18 and improving product labels have only modest supporting evidence. For example, computerized practitioner order entry has decreased medication errors in several studies but has not significantly reduced actual adverse drug events.…”
mentioning
confidence: 99%